Risk factors associated with vaginal vault hematoma infection following vaginal hysterectomy - García Valderrrama, Freddy (2015)
Objectives: To determine risk factors associated with vaginal vault hematoma infection following vaginal hysterectomy. Design: Retrospective, descriptive, casecontrol study. Setting: Department of Obstetrics and Gynecology, Hospital Nacional Arzobispo Loayza, Lima, Peru. Participants: Women subjected to vaginal hysterectomy. Methods: Ninety clinical charts (30 cases, 60 controls) of patients subjected to vaginal hysterectomy during 2008-2009 were reviewed. Statistical analysis used SPSS 17.0 program, as all variables were adapted to qualitative denomination and as the dependent variable was dichotomic we used simple and multiple logistic regression analysis to determine association and confusion variables. We considered significative p < 0,05. Main outcome measures: Infected vaginal vault hematoma. Results: Infected vault hematoma prevalence was 6.1%. Multiple logistic regression analysis showed statistically significance with variables age (OR 3.5, 95%CI 1.3–9.6, p < 0.05), body mass index (OR 6, 95%CI 2.1–17.4, p < 0.05) and estimated post operative blood loss (OR 4.3, 95%CI 1.3- 13.8, p < 0,05). Lineal regression analysis showed statically significance between estimated post operative blood loss and hemoglobin variation, p<0.05. Conclusions: Age, body mass index and estimated post operatory blood loss were associated with post vaginal hysterectomy infected vaginal vault hematoma.